Peran Aktivitas Fisik dalam Mencegah Penyakit Degeneratif pada Lansia - Raudatul Jannah; Deni Firmansyah; Ariyadi Ariyadi (Journal of Medical and Health Science, 2025)
Increasing life expectancy has resulted in a growing elderly population, making them vulnerable to various degenerative diseases. Diseases such as musculoskeletal, cardiovascular, metabolic, and neurodegenerative disorders pose a major challenge in maintaining the quality of life of the elderly. Physical activity is considered an effective and sustainable non-pharmacological preventive strategy to reduce the risk of these degenerative diseases. This study aims to comprehensively examine the role of physical activity in preventing degenerative diseases in the elderly, based on the latest scientific evidence. This study used a systematic literature review design with a descriptive-analytical approach. Data were obtained from fully open-access national and international journal articles published within the last ten years. The literature analyzed encompassed various research designs, focusing on physical activity and its impact on the health of the elderly. The research process involved identification, selection, data extraction, and thematic analysis and synthesis of findings. The study results indicate that regular physical activity appropriate to the abilities of the elderly plays a significant role in preventing degenerative diseases. Physical activity has been shown to improve musculoskeletal function, cardiovascular health, metabolic control, and support mental health and cognitive function in the elderly. Furthermore, physical activity contributes to increased independence and quality of life in the elderly. The conclusion of this study confirms that physical activity is a crucial component of promotive and preventive health efforts for the elderly, and it needs to be integrated into health care and community empowerment programs.